When fate hands you lemons: A moderated moderation model of bullying victimization and psychological distress among Chinese adolescents during floods and the COVID-19 pandemic - Zhang, Yuchi; Jia, Xiaoyu (Frontiers in Psychology, 2023)
Background Bullying is a major problem worldwide and has numerous detrimental effects on the mental health of victims. The link between bullying and psychological distress in adolescents is well known. However, few studies have analyzed the impact of combined interpersonal, peer, and cultural factors on psychological distress using a social-ecological system framework in Eastern countries. Negotiable fate is a cultural belief common in Eastern societies that suggests that people can negotiate with fate for more control by exercising personal agency within the limits of what fate has determined. This study examined the moderating effects of neuroticism and negotiable fate on the relationship between bullying victimization and psychological distress among Chinese adolescents. Moreover, human society commonly suffers from multiple disasters that lead to severe mental health problems. There are few empirical studies on the effects of bullying among adolescents in multiple disaster contexts. This study included participants who experienced floods and COVID-19 simultaneously in 2021. Materials and methods We conducted a cross-sectional cluster sampling study from August 6 to 9, 2021, approximately 2 weeks after the start of the Zhengzhou City flooding and 7 days after the new wave of the COVID-19 outbreak in Zhengzhou City. The study included 1,207 participants (52.4% men, n = 633; Mage = 14.36, SD = 0.94) from a middle school in Zhengzhou City, China. Results The results revealed that bullying was positively linked to psychological distress (β = 0.5.34, p < 0.001, [0.73, 9.95]). Neuroticism and negotiable fate significantly moderated the relationship between the effects of bullying and psychological distress (β = −3.58, p < 0.05, 95% CI [−6.12, −1.04]). Specifically, high neuroticism increased the risk of psychological distress in adolescents bullied before a disaster. High or low neuroticism and high negotiable fate buffered the link between bullying and psychological distress. Conclusion This study showed that neuroticism and negotiable fate moderated the relationship between bullying victimization and psychological distress in Chinese students with COVID-19 and flood disasters. High negotiable fate and high or low neuroticism could help adolescents bullied in school to be immune from psychological distress in catastrophe. The results highlight the importance of considering the interplay between bullying, neuroticism, and a sense of controllable destiny when examining adolescents’ psychological distress.